INFLUENCE OF CONSUMPTION OF PROBIOTIC DAIRY YOGURT ON GUT MICROBIOME STRUCTURE - Pernebek , Zh.; Babenko, D.; Tarzhanova , D.; Uyzbaeva , I.; Khassenbekova , Zh.; Kozhakhmetova , S.; Kushugulova , A.; Kozhakhmetov, S. (Eurasian Journal of Applied Biotechnology, 2022)
This study shows the potential of probiotic dairy product to modulate the gut microbiota. The effect of the product on the intestinal microflora was determined by examining the fecal microflora of rats before and after 4 weeks of adding a fermented milk probiotic product to the diet. Structural changes in the faecal microflora were studied on the basis of sequencing V1-V3 hypervariable target region 16S rRNA gene. Sequencing results showed a decrease in microbiota biodiversity after taking a probiotic product. Nevertheless, enrichment of the microflora with butyrate-producing microorganisms Lachnospiraceae, Ruminococcaceae, Lactobacillales and depletion of Porphyromonadaceae, Eggerthella, Romboutsia, Fusicatenibacter and Bacillus, which are not belong to the order Lactobacillales.